Neurofibromin specific antibody differentiates malignant peripheral nerve sheath tumors (MPNST) from other spindle cell neoplasms - Reuss, David; Habel, Antje; Hagenlocher, Christian; Mucha, Jana; Ackermann, Ulrike; Tessmer, Claudia; Meyer, Jochen; Capper, David; Moldenhauer, Gerhard; Mautner, Victor; Frappart, Pierre-Olivier; Schittenhelm, Jens; et al. (Acta neuropathologica, 2014)
Malignant peripheral nerve sheath tumors (MPNST) derive from the Schwann cell or perineurial cell lineage and occur either sporadically or in association with the tumor syndrome neurofibromatosis type 1 (NF1). MPNST often pose a diagnostic challenge due to their frequent lack of pathognomonic morphological or immunohistochemical features. Mutations in the NF1 tumor suppressor gene are found in all NF1-associated and many sporadic MPNST. The presence of NF1 mutation may have the potential to differentiate MPNST from several morphologically similar neoplasms; however, mutation detection is hampered by the size of the gene and the lack of mutational hot spots. Here we describe a newly developed monoclonal antibody binding to the C-terminus of neurofibromin (clone NFC) which was selected for optimal performance in routinely processed formalin-fixed and paraffin-embedded tissue.